2020
DOI: 10.2147/dmso.s266277
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolic Score for Visceral Fat (METS-VF) Estimation – A Novel Cost-Effective Obesity Indicator for Visceral Adipose Tissue Estimation</p>

Abstract: Background Visceral adipose tissue (VAT) assessment is limited in clinical practice due to expensive, time consuming and limited availability of MRI and DXA machines. We explored the utility of a recently developed Metabolic Score for Visceral Fat (METS-VF) to assess VAT in south Asian individuals with morbid obesity. Patients and Methods Individuals with BMI ≥35 kg/m 2 aged between 30 and 60 years were randomly selected from a database of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In a Mexican urban population, METS-VF was validated as a better performing predictor of T2DM incidence compared to other surrogate VAT indexes, including visceral adiposity index (VAI) and lipid accumulation product (LAP) (6) . One study to date, in southern Indian individuals with morbid obesity (7) , has validated the utility of METS-VF as a surrogate measure of visceral adiposity, while another retrospective cohort study from China indicated that METS-VF could be a useful tool for the hierarchical prevention and management of hyperuricemia among non-obese women (8) . So far, however, no published studies have explored the relationship between METS-VF and T2DM risk in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…In a Mexican urban population, METS-VF was validated as a better performing predictor of T2DM incidence compared to other surrogate VAT indexes, including visceral adiposity index (VAI) and lipid accumulation product (LAP) (6) . One study to date, in southern Indian individuals with morbid obesity (7) , has validated the utility of METS-VF as a surrogate measure of visceral adiposity, while another retrospective cohort study from China indicated that METS-VF could be a useful tool for the hierarchical prevention and management of hyperuricemia among non-obese women (8) . So far, however, no published studies have explored the relationship between METS-VF and T2DM risk in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…A study with a larger sample size would also enable studying the impact of individual comorbidities on bone health in people with morbid obesity. Moreover, since the BMI is not the best marker for an obesity assessment, especially in the South Asian region [ 26 , 30 , 32 ], the relationship of other obesity indicators (waist−height ratio, visceral adiposity assessment, body fat percentage, lean mass, etc.) with bone health should be studied in future cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-five subjects with morbid obesity (BMI ≥ 35 kg/m 2 ) were recruited from the multidisciplinary obesity clinic in the hospital, and they were compared to 80 subjects with obesity (BMI ≥ 25–35 kg/m 2 ) and 85 non-obese women (BMI ≤ 25 kg/m 2 ) recruited from the community. The BMI cut-off points for obesity were defined as per the Asia-Pacific guidelines by the WHO, which suggest lower thresholds for obesity to identify the higher at-risk individuals at a lower BMI [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. This study was approved by the Institutional Review Board (IRB Min no.…”
Section: Methodsmentioning
confidence: 99%
“…BMI, waist circumference, and fat composition measure the severity of obesity, whereas the relative distribution of fat over various sites of the body provides an overview of its metabolic impact. [ 10 ] The swiftness with which obesity develops, reverses, or recurs, offers insights regarding the etiology of the disease, behavior of the patient, and appropriate therapeutic options. Adipose topography gives diagnostic clues to the etiology of various disorders like in Cushing's syndrome there is one particular pattern of fat distribution predominantly over the trunk, upper torso, and face.…”
Section: B Arophenotypic P Ersonalitymentioning
confidence: 99%